Age-dependent differences in cervical artery dissection - Metso, Tiina M.; Grond-Ginsbach, Caspar; Brandt, Tobias; Kloss, Manja (Journal of neurology, 2012)
The goal of this work was to explore age-dependent differences in cervical artery dissection (CeAD). This study is based on the Cervical Artery Dissection and Ischemic Stroke Patients population comprising 983 consecutive CeAD patients and 658 control patients with a non-CeAD ischemic stroke (IS), frequency-matched for age and gender. Patients were divided into three age categories: ≤33 (for CeAD, n = 150), 34-54 (n = 688), and ≥55 (n = 145) years, and the youngest and oldest groups were compared. The youngest patients were mostly women and the oldest men. The frequency of internal carotid artery dissection (ICAD) versus vertebral artery dissection (VAD) increased with age from 44 to 75 %. This age-related shift remained significant after adjustment for sex. The frequency of a transient ischemic event as the CeAD symptom declined from 33 % in the youngest age group, to 19 % in the oldest. Vascular risk factors increased in frequency with advancing age in both groups, but for hypertension the increase was steeper for non-CeAD IS patients. For CeAD patients, but not for patients with non-CeAD IS, preceding infection was more common in the oldest group. The youngest non-CeAD IS patients had better functional outcome (modified Rankin Scale 0-1) than the oldest, while the similar trend was not statistically significant among CeAD patients. Younger age seems to be associated with VAD and female gender, and older age with ICAD and male gender. Age-related changes in the frequencies of hypertension and recent infection were different between the CeAD and non-CeAD IS groups. Age does not seem to be an important outcome predictor in CeAD strokes.
Gesehen am 22.11.2018